Inconsistency of translating medical abbreviations and acronyms into the Arabic language - Siddig Mohammed (Peoples' Friendship University of Russia (RUDN University), 2022)
The paper identifies the challenges of translating variants of medical documents that include acronyms and abbreviations, which are standard in medicine, pharmacology, and healthcare contexts and documents, thus intending to examine the inconsistency of abbreviation and acronym use in a medical context. The study adopts the descriptive approach to investigate the inconsistency of medical abbreviations in English that include multiple medical meanings/versions of acronyms and abbreviations to be translated into Arabic. The samples considered in this study are documents frequently utilised in the medical context in hospitals, including graphic signs, medical reports, admission forms, and prescriptions. The documents included 18 medical abbreviations and acronyms to be translated from English into Arabic. The results revealed that the abbreviations and acronyms used in medical documents showed a discrepancy in the translation, and many versions of translations are possible. Therefore, the findings underpinned the main challenges of translating acronyms and abbreviations from English as a source language into Arabic as a target language and the consequentiality of training for the medical translators to overcome these challenges. The study concludes that medical abbreviations, acronyms, and initialisms are more frequent and multi-version and lack consistency in several documents, including medical reports, resulting in many challenges. This may also lead to erroneous versions in translation. Thus, it is recommended translators' vigilance be raised to overcome the obstacles that impede translation accuracy.